2021
DOI: 10.1021/acs.nanolett.1c01236
|View full text |Cite
|
Sign up to set email alerts
|

Accessing and Assessing the Cell-Surface Glycocalyx Using DNA Origami

Abstract: The cell-surface glycocalyx serves as a physiological barrier regulating cellular accessibility to macromolecules and other cells. Conventional glycocalyx characterization has largely been morphological rather than functional. Here, we demonstrated direct glycocalyx anchoring of DNA origami nanotiles and performed a comprehensive comparison with traditional origami targeting to the phospholipid bilayer (PLB) using cholesterol. While DNA nanotiles effectively accessed single-stranded DNA initiators anchored on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…It was clearly revealed that the cell cluster ratio increased with the increasement of PDL concentration, which reached a plateau at 100 nM. In comparison to Ramos cells, the cluster proportion of NCM460 cells was much lower, which might be attributed to the intrinsic properties of the types of cells, such as difference in cell size, membrane fluidity, and the glycocalyx structures …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It was clearly revealed that the cell cluster ratio increased with the increasement of PDL concentration, which reached a plateau at 100 nM. In comparison to Ramos cells, the cluster proportion of NCM460 cells was much lower, which might be attributed to the intrinsic properties of the types of cells, such as difference in cell size, membrane fluidity, and the glycocalyx structures …”
Section: Resultsmentioning
confidence: 96%
“…In comparison to Ramos cells, the cluster proportion of NCM460 cells was much lower, which might be attributed to the intrinsic properties of the types of cells, such as difference in cell size, membrane fluidity, and the glycocalyx structures. 45 Next, homogeneous cell fusion of Ramos cells or NCM460 cells was induced by treating PDL-clustered cells with PEG. As illustrated in Figures 3E,F and S7, we hardly observed merged yellow cells in the "no treatment" group, indicating that no fluorophore transfer occurred between cells during 24 h of cell culture, while a small percentage of fused cells were observed in the PEG groups for both cell types (4.28% for Ramos, 3.25% for NCM460), in alignment with the results reported in the literature.…”
Section: Homogeneous Cellmentioning
confidence: 99%
“…Wijesekara et al recently established DNA origami nanostructures as a functional measure of cellsurface glyco calyx barrier integrity, offering an expanded toolbox for cell surface targeting using DNA origami to modulate intercellular and intracellular activities. [189] Except for the detection of membrane components, cell sur faceanchored nucleic acidbased sensors can be applied to cel lular activities or intercellular interactions. Receptor clustering (e.g., receptor dimerization and receptor oligomerization) is considered a general mechanism for activating receptors, which regulate many signaling pathways.…”
Section: Engineering Cell Surfaces For Biosensingmentioning
confidence: 99%
“…recently established DNA origami nanostructures as a functional measure of cell‐surface glycocalyx barrier integrity, offering an expanded toolbox for cell‐surface targeting using DNA origami to modulate intercellular and intracellular activities. [ 189 ]…”
Section: Biointerface Engineering With Nucleic Acid Materialsmentioning
confidence: 99%
“…EC-glycocalyx is mainly comprised of a network of core proteins and branching glycosaminoglycan polymers such as heparan sulfate (HS), chondroitin sulfate (CS), and hyaluronans (HA), respectively (van den Berg et al, 2003;Lipowsky, 2012;Yamaoka-Tojo, 2020;Urschel et al, 2021;Wijesekara et al, 2021). The most common of which is HS, which are anchored to endothelial cells (ECs) via transmembrane proteoglycans and always released from the endothelium upon glycocalyx injury.…”
Section: Introductionmentioning
confidence: 99%